Use of Computed Tomography – Digital Subtraction Angiography in differentiating pulmonary thrombosis and pulmonary artery dissection in a large pulmonary artery aneurysm - Rashid, Hashrul N.Z. (Respir Med Case Rep, 2016)
70 year-old female with chronic obstructive pulmonary disease (COPD) presented with typical symptoms of an exacerbation of COPD. Management of COPD resolved her wheezing, but ongoing hypoxia and retrospective history of atypical chest pain prompted exclusion of a pulmonary embolus. A CT Pulmonary Angiogram (CTPA) with standard 64-slice CT revealed an extensive non-occlusive defect in a grossly dilated right pulmonary artery. Presence of circumferential cuff of soft tissue within sub-segmental pulmonary artery branch raised the possibility of pulmonary artery dissection (PAD). Exclusion of PAD was important as it precluded full anticoagulation. A dynamic CT-digital subtraction angiography (CT-DSA) with the 320-slice multidetector CT (Aquilion-one Vision, Toshiba) did not reveal any intimal flap or contrast extension into the pulmonary arterial wall, suggesting it is unlikely to be PAD. The patient was started on full anticoagulation and reported improvement of symptoms with reduction in pulmonary thrombus burden on repeat CTPA at 4 weeks. To our knowledge, this is the first reported use of dynamic CT-DSA in ruling out PAD.